An Analysis of Spatial Pathology of the Physical and Social Structure of the City with Non-Relevant Defense Approach Case Study: Tehran Metropolitan Area - s z; a t; m a (تحقیقات کاربردی علوم جغرافیایی)
Using the passive defense principles in urban plans and projects is important in the context of land use planning, reinforced concrete, citizen education, and increasing urban resiliency. Observing and adhering to these principles will reduce the vulnerability of the city and citizens to security and military threats. Therefore, this study aims at evaluating the spatial pathology of the physical and social structure of the 6th urban district of Tehran municipality with emphasis on passive defense approach principles particularly citizenship education principle. Therefore, this research has selected the 6th urban district of Tehran municipality, due to its important and sensitive land uses with regional and trans-regional functions as a research area. In this study, the AHP model was used to assess the physical structure pathology. In order to evaluate the social structure damages of the area, three neighborhoods were selected in the region using cluster-spatial sampling. Then, using the survey method, the authors sought to collect the views of the inhabitants. In order to determine the sample size, the Cochran's formula was used. The results of this study indicate that the vulnerability of the region in terms of the physical structure is moderate and downward. Additionally, the social vulnerability of the area is also above average. Finally, the factors influencing the vulnerability of physical and social structure were investigated. Accordingly, it can be concluded that the indicators of population and construction density are the most important factors affecting vulnerability from experts' viewpoint. In addition, it was revealed that education and awareness, resiliency against security-military threats, skill and expertise, respectively, are the effective indicators of the vulnerability of the social structure of the area.